The Position of Presidential Abolition in Indonesian Law: Case Study of Tom Lembong from the Perspective of Maqashid Syari'ah and Legal Benefits - Efendi, Syamsul; Wijaya, Wijaya; Aiman, Muhammad; Hakim, Dan Amran; Rahmawati, Rahmawati (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to deeply analyze the status, function, and legal implications of the President of the Republic of Indonesia's right to abolish, particularly in the context of criminal and constitutional law. Abolition, as an instrument of pardon, amnesty, and abolition (GNA), enshrined in Article 14 of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), is the prerogative of the head of state to abolish a criminal offense or halt the prosecution of a person suspected of or having committed a crime, before the trial process is complete. The strength of this right lies in its character as an instrument of judicial discretion that transcends judicial decisions, and its implementation must take into account the considerations of the House of Representatives (DPR). The study focuses on the case study of Thomas Trikasih Lembong (Tom Lembong), who, in the public narrative, has been linked to potential involvement in controversial cases. This case was chosen as a model to test the limits of the use of abolition in Indonesia. Normatively, the use of abolition in Indonesia is rare compared to pardons and amnesties, making it a gray area in constitutional practice. This study uses a juridical-normative and philosophical approach, enriched with a qualitative analysis of the relevant legal framework and constitutional law doctrine. From the perspective of Maqashid Syari'ah (Objectives of Islamic Law), abolition is analyzed based on its purpose in preserving the five basic pillars (al-Kulliyat al-Khams): preserving religion (hifz ad-din), preserving the soul (hifz an-nafs), preserving reason (hifz al-'aql), preserving descendants (hifz an-nasl), and preserving property (hifz al-mal). The appropriate use of abolition should contribute to the achievement of substantial justice and the protection of greater public interests, going beyond mere formal legal certainty. Meanwhile, from the perspective of Legal Benefit (Rechtssicherheit and Zweckmässigkeit), this study examines the extent to which the application of abolition, particularly in sensitive cases such as those involving public figures or economic interests, can provide sociological benefits, namely restoring order, preventing greater harm, or supporting national stability, without sacrificing the public's sense of justice. The study's findings indicate that although abolition is a legitimate prerogative, its use must be based on the ultra petita principles of justice and the pressing public interest, in line with the values of Maqasid Sharia and the principle of expediency. A balance between legal certainty, justice, and expediency is key to legitimizing the exercise of the president's right to abolition.